How to prevent and cope with coincidence of risks to the global food system - Fan, Shenggen; Cho, Emily EunYoung; Meng, Ting; Rue, Christopher (Annual Reviews, 2021)
The global food system faces major risks and threats that can cause massive economic loss; dislocation of food supply chains; and welfare loss of producers, consumers, and other food system actors. The interrelated nature of the system has highlighted the complexity of risks. Climate change, extreme weather events, and degradation and depletion of natural resources, including water, arable, forestry, and pastural lands, loss of biodiversity, emerging diseases, trade chokepoints and disruptions, macroeconomic shocks, and conflicts, can each seriously disrupt the system. Coincidence of these risks can compound the effects on global food security and nutrition. Smallholder farmers, rural migrants, women, youth, children, low-income populations, and other disadvantaged groups are particularly vulnerable. The coronavirus disease 2019 (COVID-19) pandemic exemplifies a perfect storm of coincidental risks. This article reviews major risks that most significantly impact food systems and highlights the importance of prospects for coincidence of risks. We present pathways to de-risk food systems and a way forward to ensure healthy, sustainable, inclusive, and resilient food systems.